Diskrepansi Sanksi Adat terhadap Pelaku Tindak Pidana Pencurian Menurut Tokoh Adat dan Tokoh Agama - Asnawi, M. Halim; Hadi, Sutrisno (Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the discrepancy of customary sanctions that occur to perpetrators of the crime of theft by taking the point of view of the opinions of traditional leaders and religious leaders. This research was conducted in Manggar Raya Village, Banyuasin. This research is a type of field research research by making the results of interviews as primary data sources and books, journals, theses and articles as secondary data sources. This article is arranged systematically according to a series of events that occur collectively and deductively. Based on the results of research and discussion of the discrepancy of customary sanctions against perpetrators of the crime of theft, it is true. In the 1989 incident, the perpetrator was sentenced to half-body burying, the 2014 incident was sentenced to drag from the upstream and downstream of the village, and in the 2019 incident the perpetrator was sentenced to 5 years of exile. However, in its application it is not in accordance with what has been agreed upon and causes unrest in some people. According to traditional leaders and religious leaders, the discrepancy in customary sanctions was caused by several factors, namely the emotional level of the residents of Manggar Raya Village, the number of people belonging to the lack of understanding of the law, kinship and the perpetrators of theft disobeyed the agreed sanctions or the perpetrators of theft rebelled when the sanctions were imposed applied.